Reclassification of the biocontrol agents Bacillus subtilis BY-2 and Tu-100 as Bacillus velezensis and insights into the genomic and specialized metabolite diversity of the species. Issue 12 (9th December 2020) - Mullins, Alex J.; Li, Yinshui; Qin, Lu; Hu, Xiaojia; Xie, Lihua; Gu, Chiming; Mahenthiralingam, Eshwar; Liao, Xing; Webster, Gordon
Abstract : The genomes of two historical Bacillus species strains isolated from the roots of oilseed rape and used routinely in PR China as biocontrol agents to suppress Sclerotinia disease were sequenced. Average nucleotide identity (ANI) and digital DNA–DNA hybridization analyses demonstrated that they were originally misclassified as Bacillus subtilis and now belong to the bacterial species Bacillus velezensis . A broader ANI analysis of available Bacillus genomes identified 292 B. velezensis genomes that were then subjected to core gene analysis and phylogenomics. Prediction and dereplication of specialized metabolite biosynthetic gene clusters (BGCs) defined the prevalence of multiple antimicrobial-associated BGCs and highlighted the natural product potential of B. velezensis . By defining the core and accessory antimicrobial biosynthetic capacity of the species, we offer an in-depth understanding of B. velezensis natural product capacity to facilitate the selection and testing of B. velezensis strains for use as biological control agents.